Visual Studio LightSwitch 2015 - Leung, Tim (Expert's voice in .NET., 2015)
In this fully updated second edition, award-winning author Tim Leung explains how to build data-centric business applications for the desktop, cloud, web, and mobile devices in just a few clicks--with no code required--using Visual Studio Lightswitch 2015. This book explains the basics of Visual Studio Lightswitch 2015 plus new features and key advanced topics that every Microsoft developer needs to know to create modern data services and build clients that can run on multiple devices. Visual Studio LightSwitch 2015 is a rapid application deployment tool that simplifies and shortens the time needed to develop business applications. The basics are very easily understood but more advanced users will hunger for more. How do you design complex layouts? How do you query data using LINQ and other syntax structures? How do you secure your application against malicious use? Visual Studio LightSwitch 2015 answers these questions and more as author Tim Leung--winner of a Microsoft 2011 Community Contributor Award for his LightSwitch expertise--covers this breakthrough product in detail. For serious developers building, enhancing, and deploying advanced business applications using LightSwitch makes sense because they can benefit from the elegance, convenience, and cost savings afforded by rapid application development before going beyond the "click-and-you're-done" interface to include the extra value and depth of coding expertise that their clients value.